Genetic correlation and path coefficient analysis in groundnut (Arachis hypogaea L.) - Alam, MK (SAARC Journal of Agriculture, 2014)
Correlation and path co-efficient analysis were carried out for pod yield and its yield components characters in 45 genotypes of groundnut. The genotypic correlation co-efficient were found to be of relatively higher magnitude than the corresponding phenotypic correlation co-efficient, indicating strong inherent association between the characters. Pod yield showed significant positive association with secondary branches/plant, harvest index, 100-pod weight, 100-kernel weight, pod size, diseases incidence and canopy temperature. Path co-efficient analysis revealed high direct effects of primary branches/plant, secondary branches/plant and harvest index. Hence, it would be rewarding to give due importance on the selection of these characters for rapid improvement in pod yield of groundnut. DOI: http://dx.doi.org/10.3329/sja.v12i1.21116 SAARC J. Agri., 12(1): 96-105 (2014)